ADAPTASI MODEL SOLIDARITAS PEMIKIRAN SYEIKH AHMAD YASSIN UNTUK PENGUATAN SOLIDARITAS KEINDONESIAAN: (Adaptation of Sheikh Ahmad Yassin's Solidarity Model to Strengthen Indonesian Solidarity) - Ekki Suryana Zaen; Muhammad Fahmy bin Rapaee; Muhammad Firdaus (Raqib: Jurnal Studi Islam, 2025)
Religiously-informed social leadership plays a crucial role in strengthening community solidarity, particularly amid identity crises, conflicts, or structural development challenges. This research analyzes the architecture of solidarity built by Sheikh Ahmad Yassin (1937-2004), the founder of Hamas, in Palestine, and adapts his conceptual strategies into the framework of Indonesian nationhood (Konsep Keindonesiaan). Although studies on Yassin often focus on the political and military dimensions of resistance, this analysis posits that his success lies in a unique and multidimensional strategy: the institutionalization of solidarity, which strategically filled humanitarian and social vacuums through the establishment of educational, welfare, and health institutions. Using a functional comparative and hermeneutic approach, key findings indicate that the pillars of Yassin’s movement, namely (1) moral leadership derived from physical weakness, (2) the institutionalization of social services as a political pre-condition, and (3) a multidimensional struggle ideology integrating spiritual and material aspects, hold significant functional relevance for the role of Islamic social organizations (Ormas Islam) in Indonesia. This conceptual adaptation transforms Yassin’s concept of Jihad of Resistance (against occupation and maintaining land as waqaf) into Jihad of Development within the Indonesian Context. Jihad of Development is understood as a collective, structured, and continuous effort by Ormas Islam to overcome the nation’s structural weaknesses (such as stunting and poverty), thereby strengthening social resilience and consolidating Indonesian religious nationalism based on the universal principle of kemaslahatan (public benefit).